2016
DOI: 10.1002/2211-5463.12032
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: microRNA‐497 inhibits cell proliferation and induces apoptosis by targeting YAP1 in human hepatocellular carcinoma

Abstract: micro RNA s (mi RNA s) function as oncogenes or tumor suppressors in human cancers by targeting mRNA s for degradation and/or translational repression. miR‐497 has been proposed as a tumor suppressive mi RNA and its deregulation is observed in human cancers. However, the prognostic value of miR‐497 and its underlying molecular pathways involved in the initiation and development of hepatocellular carcinoma ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 26 publications
(29 reference statements)
2
27
0
Order By: Relevance
“…Previous studies have shown that miR-497 can act as a tumor suppressor, including in HCC. 24,25 The regulatory relationship between LINC02476 and miR-497 was confirmed by the following data: 1) LINC02476 downregulation increased the expression of miR-497; 2) a luciferase activity assay confirmed the direct binding to the predicted miR-497 binding site on LINC02476; 3) the RIP assay confirmed thatLINC02476 and miR-497 were in the same RNAinduced silencing complex. In our study, HMGA2 was identified as a downstream target of miR-497.…”
mentioning
confidence: 73%
“…Previous studies have shown that miR-497 can act as a tumor suppressor, including in HCC. 24,25 The regulatory relationship between LINC02476 and miR-497 was confirmed by the following data: 1) LINC02476 downregulation increased the expression of miR-497; 2) a luciferase activity assay confirmed the direct binding to the predicted miR-497 binding site on LINC02476; 3) the RIP assay confirmed thatLINC02476 and miR-497 were in the same RNAinduced silencing complex. In our study, HMGA2 was identified as a downstream target of miR-497.…”
mentioning
confidence: 73%
“…YAP1 was upregulated in HCC tissues and cells, and promoted HCC development and progression [24]. In addition, recently miR-497 and miR-506 were reported to inhibit cell proliferation and induce apoptosis by targeting YAP1 in HCC [31, 32]. Therefore, we speculated that miR-199a-3p might target YAP1 to regulate HCC cell proliferation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of TargetScan database and previous studies [16,17,32,33] revealed that 3' UTRs of YAP, SMAD3, CCND1 and BIRC5 contained at least one conserved binding site for miR-497 ~ 195 cluster (Fig. 4B).…”
Section: Mir-497 and Mir-195 Directly Suppressed Multiple Key Componementioning
confidence: 59%